2010
DOI: 10.1017/s1743921310016145
|View full text |Cite
|
Sign up to set email alerts
|

GRS 1915+105 “celebrates its majority” (1992–2010)

Abstract: Abstract. Over the 18 years since its discovery, GRS 1915+105 has continuously brightened in the X/γ-ray sky. It is considered the prototypical microquasar. Most of these are LMXBs that show sporadic ejection of matter at apparently superluminal velocities. In these the three basic ingredients of quasars are found: a black hole, an accretion disc and collimated jets of high energy particles, but in microquasars the black hole is only a few M instead of several × 10 6 M ; the accretion disc had mean thermal tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, further investigations over radio, optical, and X-ray bands are needed to specifically address the reason of radio lead for this atypical outburst. -Tirado et al (1992) discovered GRS 1915+105 using WATCH on board GRANAT satellite. Apparent superluminal jets were detected (Mirabel & Rodríguez (1994)).…”
Section: H 1743-322mentioning
confidence: 99%
“…However, further investigations over radio, optical, and X-ray bands are needed to specifically address the reason of radio lead for this atypical outburst. -Tirado et al (1992) discovered GRS 1915+105 using WATCH on board GRANAT satellite. Apparent superluminal jets were detected (Mirabel & Rodríguez (1994)).…”
Section: H 1743-322mentioning
confidence: 99%
“…GRS 1915+105 was discovered in 1992 by the WATCH ASM aboard GRANAT (Castro-Tirado et al 1992) and has remained active ever since (Belloni & Altamirano 2013). The system exhibits very peculiar behavior, in the form of complex structured variability, such as QPOs ranging in frequency from 10 −3 Hz to 67 Hz and patterns of dips and rapid transitions between high and low intensity in the light curve (Greiner et al 1996;Morgan et al 1997;Belloni et al 2000;Klein-Wolt et al 2002;Fender & Belloni 2004;Hannikainen et al 2005).…”
Section: Grs 1915+105 (A)mentioning
confidence: 99%
“…GRS 1915+105 is one of the well known LMXBs whose behavior at the high luminosity regime is fairly well characterized and extensively studied in outburst (Belloni et al 2000). Since the discovery outburst in 1992 (Castro-Tirado et al 1992), an exponential decay of its X-ray emission has been observed a few times (Negoro, et al 2018). The source also exhibited et al (2006); Miller-Jones et al (2008) has also become an interesting scheme to explain the spectral properties of Xray binaries in quiescence (Miller-Jones et al 2011;Plotkin et al 2016).…”
Section: Introductionmentioning
confidence: 99%